International models, trends and concepts of the philosophy of education in the context of sustainable social development under global institutional transformation conditions - Viktor Zinchenko (Cхід, 2019)
At the turn of the Millennium, the issue of education, especially higher education, its role in state formation and impact on the life of society acquired particular relevance and became a subject of research of not only teachers and historians but also economists, political analysts, psychologists, social scientists and, above all, philosophers (which gave rise to a variety of models and trends in the philosophy of education). In the meantime, there is some lack of fundamental integrative studies into comprehensive educational-managerial and socio-historical, socio-economic and state-political experiences of some developed countries in the implementation of these philosophical and educational paradigms, trends, models and reforming/modernization concepts of higher education and science, to be examined with consideration for similar challenges faced by education and science in Ukraine. Nearly every developed country has wide experience in building up a system of higher education. Results of reviewing such experience may contribute to the development and enrichment of the domestic educational system, afford an opportunity to avoid repeating mistakes and offer new approaches to solving a range of problems in this field. Based on the above, we also believe that it is impossible to pretend to develop a strategy for educational and scientific modernization reforms that deal with challenges of educational and scientific institution of society in management of scientific and educational space (which applies to both a social component of the philosophy of education and the field of educational management) without analyzing the existing models, schools, trends and their classification in the modern philosophy of education.